How to successfully administer palliative treatment with a stent for malignant gastric outlet obstruction? - Maetani, Iruru (Frontiers in Medicine, 2022)
Although endoscopic stenting (ES) has been widely used as a less-invasive palliation method for malignant gastric outlet obstruction (GOO), recent reports have highlighted issues related to the procedure. For successful treatment, various aspects must be assessed before considering the practices. First, it is necessary to eliminate cases with contraindications such as coexistence of distal small-bowel obstruction or perforation. Other factors potentially related to clinical failure (i.e., peritoneal carcinomatosis) may require consideration but remain controversial. ES has better short-term outcomes than surgical gastrojejunostomy (GJ). GJ has recently been considered preferable in cases with longer life expectancy because of superior sustainability. Various types of stents are now commercially available, but their ideal structure and mechanical properties have not yet been clarified. Covered metal stent may reduce stent obstruction but is prone to increase stent migration, and its significance remains uncertain. Subsequent chemotherapy after stenting should be considered, as it is expected to prolong patient survival without increasing the risk of adverse events. Furthermore, it may be helpful in preventing tumor ingrowth. In cases with GOO combined with biliary obstruction, biliary intervention is often difficult. Recently, endoscopic ultrasound-guided biliary drainage (EUS-BD) has been widely used as an alternative procedure for endoscopic transpapillary biliary drainage (ETBD). Despite the lack of consensus as to whether ETBD or EUS-BD is preferred, EUS-BD is useful as a salvage technique for cases where ETBD is difficult. To perform stent placement successfully, it is important to pay attention to the above points; however, many remaining issues need to be clarified in the future.